Acne during Covid-19-The effect of pandemic and quarantine on skin care of patients with acne - Patrycja Niewinna; Klaudia Kołodziej; Michał Żuchowski; Dominika Mańdziuk; Przemysław Zaroda; Paweł Dąda; Paweł Pawlik; Wojciech Kołodziej; Jakub Wawrzkowicz; Monika Korga (Nicolaus Copernicus University in Toruń, 2024)
Introduction:Acne is a chronic inflammatory disease of the pilosebaceous unit resulting from androgen-induced increased sebum production, altered keratinisation, inflammation, on the face, neck, chest and back.[1] During the COVID-19 pandemic, many patients with acne complained of worsening symptoms. This investigation was designed to survey the impact of COVID-19 regulations on acne and guide patients with acne on symptom management during the pandemic.[2] Aim of the study:The study aimed to investigate whether the problem of acne increased during the pandemic.Has the pandemic affected the level of people's awareness of acne and skin care?Did wearing masks affect the condition of the skin?  Methods and Materials:Research was conducted on a group of 484 people (female - 97%, male - 3%).The study group included patients who suffered from acne before the pandemic and patients who developed it during the pandemic (from March 2020).  Results:The conducted research confirms that the restrictions introduced during the COVID-19 pandemic (face masks) had a significant impact on the skin condition of patients with acne and their care habits. Patients' interest in the subject of acne and involvement in the treatment has increased significantly - that is a positive trend. Conclusion: The COVID-19 pandemic has given rise to the need to use personal protective equipment such as masks.[4]The use of face masks is associated with high rates of acne eruption.[5]Patients with acne vulgaris continue to present increasingly in dermatology outpatient clinics and seek treatment during the COVID-19 pandemic.[6] Patients during COVID-19 intensify their dermatology treatment.